Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing